IMUNITAS DAN KESEHATAN TUBUH MELALUI AKTIVITAS OLAHRAGA YANG EFEKTIF - Nimrot Manalu; Ibrena Tarigan; Nurul Ikhwani; Win Sara Diwa; Zaskia Al Yasmin Saragih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of sports activities on immunity and body health. This study used a quantitative method with a survey approach. The research sample was determined using a purposive sampling technique with a total of 30 respondents who exercise at least 2–3 times a week. The results showed that the majority of respondents had a high level of sports activity (46.7%), while the majority of respondents' health conditions were in the good category (50%). The results of the Pearson Product Moment correlation test showed a correlation coefficient value of r = 0.72 with a significance value of 0.000 < 0.05. Based on the results of the study, it can be concluded that effective and regular sports activities have a positive influence on immunity and body health.